Race, Racialization and Antiracism in Canada and Beyond - Enomoto, Randy, 1944-; Johnson, Genevieve Fuji (Book collections on Project MUSE., 2007)
The intent of Race, Racialization, and Antiracism in Canada and Beyond is to probe systemic forms of racism, as well as to suggest strategies for addressing them.